Proses Komunikasi Pemasaran Personal Selling (Studi Deskriptif Kualitatif pada Penjualan Produk Herbal Bio7 PT. Unimex Power Distributor Cabang Kuningan) - Pandu Bimantara (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Abstract This research departs from the communication process used by PT. Unimex Power Distributor Kuningan branch in promoting Bio7 herbal products offered to consumers. Communication process used is by personal selling, where the sales process is done directly (face to face). The purpose of this research are: 1) Understanding the stages of personal selling communication process conducted by sales in increasing customer loyalty to the sale of herbal products Bio7. 2) Understanding the media used by sales in promoting the sale of Bio7 herbal products. 3) Understanding the obstacles faced by sales in conducting personal selling communication process in selling Bio Seven herbal products. This research uses qualitative research method with approach or paradigm of constructivism. Based on the approach, then the analysis of the blade that the author uses is with case study techniques. The results showed that (1) that the process of personal selling communications made by sales PT. Unimex Power Distributor Kuningan branch in product marketing is very important role to the success rate of product marketing. The results of the analysis of marketing promotion mix with personal selling to the level of sale of herbal products Bio7 showed very good achievement. (2) The marketing medium used by PT. Unimex Power Distributor Kuningan branch in marketing Bio7 herbal product is using radio media. With the reason radio became one of the agents as well as a single promotional media so that it can support to advertise the product. (3) In the implementation of a marketing activity, the company is often faced with internal and external problems, the barriers from the marketing mix of personal selling made by the sales to the consumers is very minimal promotion process in the marketing of products that have been offered. Keywords: Marketing Communication, Personal Selling, Communication Media